Current Concepts in the Biopsy of Musculoskeletal Tumors. (5th June 2013) - Errani, Costantino; Traina, Francesco; Perna, Fabrizio; Calamelli, Carlotta; Faldini, Cesare
Abstract : In the management of bone and soft tissue tumors, accurate diagnosis, using a combination of clinical, radiographic, and histological data, is critical to optimize outcome. On occasion, diagnosis can be made by careful history, physical examination, and images alone. However, the ultimate diagnosis usually depends on histologic analysis by an experienced pathologist. Biopsy is a very important and complex surgery in the staging process. It must be done carefully, so as not to adversely affect the outcome. Technical considerations include proper location and orientation of the biopsy incision and meticulous hemostasis. It is necessary to obtain tissue for a histological diagnosis without spreading the tumor and so compromise the treatment. Furthermore, the surgeon does not open compartmental barriers, anatomic planes, joint space, and tissue area around neurovascular bundles. Nevertheless, avoid producing a hematoma. Biopsy should be carefully planned according to the site and definitive surgery and should be performed by an orthopedic surgeon with an experience in musculoskeletal oncology who will perform the definitive surgery. Improperly done, it can complicate patient care and sometimes even eliminate treatment options. Different biopsy techniques are suitable: fine-needle aspiration, core-needle biopsy, and incisional biopsy. The choice of biopsy depends on the size, the location of the lesion, and the experience of the pathologist.